The effects of executive constraints on political trust. Issue 8 (17th November 2018) - Cinar, Kursat; Ugur-Cinar, Meral
ABSTRACT: This article explores political trust, delving into its subcomponents and the relationship between them. It is interested in explaining why governmental trust and trust in regulative state institutions are similar in some countries and different in others. It argues that the variation can best be explained by checks on the executive. This is the case because the more restricted the executive, the less regulative state institutions are affected by the fluctuations in governmental trust. When the government cannot encroach upon state institutions, the impartiality and efficacy of regulative institutions are maintained. The less governmental interference to regulative state institutions, the more such institutions will be devoted to the public rather than partisan interests, resulting in a wider gap between state and government trust. The argument is tested through an empirical analysis of a cross-national panel data based on all existing waves of the World Values Survey.